Psychometric properties of the Romanian version of the female sexual function index (FSFI-RO) - Ana-Maria Cristina Daescu; Liana Dehelean; Dan-Bogdan Navolan; Gheorghe Nicusor Pop; Dana Liana Stoian (BMC, 2023)
Abstract Background Female sexual dysfunction (FSD) is a highly prevalent health disorder and no self-report questionnaire on female sexual function is available in Romanian. Therefore we considered the Female Sexual Function Index (FSFI) to be the most appropriate due to its excellent psychometric properties. The FSFI is a measuring scale with 19 items that assess the six domains of female sexual function: desire, arousal, lubrication, orgasm, satisfaction and pain. The paper aims to analyze the psychometric reliability and validity of the FSFI-RO (Romanian Version of the Female Sexual Function Index). Methods 385 women (aged 18 to 51) enrolled in the present study. To assess the presence of FSD we used the Diagnostic and Statistical Manual of Mental Disorders, 5th edition (DSM-5) criteria for sexual dysfunction. Then we categorized the participants into two groups: the FSD group (41%) and the healthy control group (59%). Women were then asked to fill out a form that included sociodemographic information and the FSFI-RO questionnaire. A sample of 50 women agreed to re-answer FSFI-RO in a 4-week interval in order to evaluate the test-retest validity of the questionnaire. The data were summarized using descriptive statistics: the test-retest reliability was measured by the intraclass correlation coefficient (ICC); Cronbach's alpha was employed to evaluate the internal consistency of the Romanian version of the FSFI, and validity was assessed by the content and construct validity. Results The results showed high test-retest reliability, with ICC from 0.942 to 0.991 in the domains and 0.987 in the total score. Regarding the internal consistency of the FSFI-RO, Cronbach's α coefficients were found to be high (α = 0.944). Convergent construct validity proved to be moderate to high in desire, arousal, lubrication, orgasm and, satisfaction domains, and weak correlation in the pain domain. Regarding the discriminant construct validity, the scores for each domain and the total score showed statistically significant differences between the FSD group and the control group. Conclusions The FSFI-RO showed similar psychometric properties to those of the original version, therefore being a reliable and valid instrument that can be used in Romanian-speaking women.